Silverlight and ASP.NET Revealed - MacDonald, Matthew (Apress, 2013)
Although the Web is easily the most popular environment for business software, there are some things that web applications just can’t do, or can’t do very well. Even if you outfit your ASP.NET web pages with the latest cutting-edge JavaScript, you won’t be able to duplicate many of the capabilities that desktop applications take for granted, such as animation, sound and video playback, and 3D graphics. And although you can use JavaScript to respond on the client to focus changes, mouse movements, and other “real-time” events, you still can’t build a complex interface that’s anywhere near as responsive as a window in a rich client application. (The saving grace of web programming is that you usually don’t need these frills. The benefits you gain—broad compatibility, high security, no deployment cost, and a scalable server-side model—outweigh the loss of a few niceties.)